2016
DOI: 10.1016/j.chest.2016.09.020
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Insomnia and Asthma Burden in the Severe Asthma Research Program (SARP) III

Abstract: BACKGROUND: Sleep difficulties are commonly reported by patients with asthma; however, the prevalence of insomnia and its association with disease burden and well-being is unknown. We aimed to determine the prevalence of insomnia, defined as combined sleep-specific complaints with associated daytime symptoms, among a large sample of adults with asthma, and to compare well-being, asthma control, and asthma-related health care utilization in individuals with asthma and insomnia and those without insomnia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
60
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(65 citation statements)
references
References 36 publications
(55 reference statements)
3
60
2
Order By: Relevance
“…A significant proportion of patients with difficult asthma report symptoms of anxiety and depression, although it is unclear to which extent these symptoms are the result of the severity of their asthma, or a contributing cause of their symptoms. In the Severe Asthma Research Population (SARP), patients with insomnia, anxiety and depression had a 2.4‐fold increased risk for poor asthma control and a 1.5 higher risk for healthcare utilization, suggestion a significant impact of these conditions on asthma‐related outcomes …”
Section: Anxiety and Depressionmentioning
confidence: 99%
See 1 more Smart Citation
“…A significant proportion of patients with difficult asthma report symptoms of anxiety and depression, although it is unclear to which extent these symptoms are the result of the severity of their asthma, or a contributing cause of their symptoms. In the Severe Asthma Research Population (SARP), patients with insomnia, anxiety and depression had a 2.4‐fold increased risk for poor asthma control and a 1.5 higher risk for healthcare utilization, suggestion a significant impact of these conditions on asthma‐related outcomes …”
Section: Anxiety and Depressionmentioning
confidence: 99%
“…In the Severe Asthma Research Population (SARP), patients with insomnia, anxiety and depression had a 2.4-fold increased risk for poor asthma control and a 1.5 higher risk for healthcare utilization, suggestion a significant impact of these conditions on asthma-related outcomes. 59 A commonly used tool for assessing potential traits of anxiety and depression is the Hospital Anxiety and Depression Scale (HADS), a validated self-assessment questionnaire containing 14 questions in total, 7 for anxiety and 7 for depression. 60,61 The highest score is 21 for each domain.…”
Section: Anxiety and Depressionmentioning
confidence: 99%
“…Anxiety and depression are prevalent conditions among patients with severe asthma, and may contribute to symptoms, but also be the result of having a severe and chronic disease [77]. Patients may be screened with questionnaires such as the Hospital depression and Anxiety Scale (HADS) [78,79], although there are as of yet no validated questionnaires for asthma specifically.…”
Section: Systematic Assessment Of Severe Asthmamentioning
confidence: 99%
“…The study showed that adult patients with asthma and comorbid GAD and/or MDD who were titrated to target doses of antidepressants had reduced risk of severe asthma exacerbations and a lower number of asthma‐related outcomes over 1‐ and 2‐year follow‐up periods compared with those who were not optimized to achieve target doses. Although the relationship between asthma and anxiety/depression is well established, to our knowledge, this study is the first to investigate whether antidepressant target dose optimization compared with not achieving antidepressant target doses will improve markers of asthma control 2–4,7–10 …”
Section: Discussionmentioning
confidence: 99%
“…3 Interestingly, many conditions exist concurrently with asthma and are associated with worsened outcomes and control. [4][5][6] Psychiatric disorders, such as anxiety and depression, were shown to be more prevalent in persons diagnosed with asthma. 7 These comorbid psychiatric conditions increase the severity of asthma-related symptoms, decrease asthma control, reduce adherence to medication therapy, and increase the use of health care services.…”
mentioning
confidence: 99%